LITERATURE REVIEW: THE POTENTIAL OF NON-EDIBLE OILS AS RAW MATERIALS FOR BIODIESEL PRODUCTION: TINJAUAN PUSTAKA: POTENSI MINYAK NON-NON-MAKAN SEBAGAI BAHAN BAKU PRODUKSI BIODIESEL - Heni Sugesti; Yogi Chandra; Isma Uly Maranggi; Wahyu Triaji Rahadianto; Eka Putri (LPPM Universitas Malikussaleh, 2025)
The global energy crisis and limited fossil fuel resources have prompted the search for sustainable alternative fuels. Biodiesel is one of the environmentally friendly renewable energy solutions that can be produced from various sources, including non-edible oils. Non-edible oils, such as karanja, jatropha, mahua, castor, neem, linseed, jojoba, and rapeseed, offer several advantages, including not competing with food crops, high lipid content, and the ability to be cultivated on marginal land. Biodiesel production from non-edible oils is carried out through a transesterification process using short-chain alcohol with the aid of catalysts, both homogeneous and heterogeneous. The study results indicate that homogeneous base catalysts achieve high conversion efficiencies under specific reaction conditions. Meanwhile, heterogeneous catalysts also provide high yields (>90%). The use of heterogeneous catalysts offers advantages in separation and recycling processes. Based on these findings, non-edible oils have proven to be a viable and strategic feedstock for the production of second-generation biodiesel. This approach supports the development of sustainable energy and the reduction of carbon emissions in the future.